Usaha Mikro Dalam Keluarga di WK Audio Sound Sistem Bogor - Aminudin Aminudin; Dedi Junaedi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2022)
This community service activity aims to identify micro, small and medium enterprises in WK Audio System Cileungsi Bogor. The method used is a field study and qualitative analysis of the operation of a family business. Based on the results of the analysis of the WK Audio Sound System business, it can be concluded: (1) the internal factors that become the main strengths of the WK audio sound system are a well-managed family business, having employees who are closely related and understand each other's sound system; (2) external factors that become the main opportunity for WK Audio Sound System, namely consumers of sound system equipment that continue to increase so that the potential to get more customers, while the main threat of WK Audio Sound System is the emergence of competitors that cause competition.